Manpower Training and Development as Organizational Tools for Effectiveness - Varma, Alok (Digital Repository of Theses - SSBM Geneva, 2025)
This dissertation examines the impact of training programs on employee performance, focusing on the effectiveness of training content, trainer engagement, soft skills development, sales training, and product knowledge. The study aims to assess how training can improve employee performance and align individual growth with organizational goals. Using a quantitative research methodology, data was collected from 200 respondents across various job positions within an organization through surveys. Statistical analyses, including ANOVA, cluster analysis, and Paired T Test, were employed to examine the data. The results indicate that training significantly improved employee performance, with positive outcomes in areas such as communication, teamwork, problem-solving, product pitching, and handling customer objections. The training also contributed to achieving sales and operational targets, enhancing employees' confidence in their roles. However, some employees, particularly those in junior or underperforming roles, showed limited improvement, suggesting the need for more personalized interventions and additional support. The study further reveals that while most participants found the training engaging and relevant, there were differences in expectations across job positions, highlighting the importance of tailoring training content to meet the specific needs of employees at different levels. The correlation between various skills developed during training suggests that a holistic approach integrating multiple competencies can enhance overall employee effectiveness. In conclusion, this dissertation emphasizes the importance of continuous skill reinforcement, personalized coaching, and more interactive learning methods in optimizing training programs. The findings offer valuable insights for organizations to design more effective training interventions that support both individual development and organizational success. Future research could focus on exploring the long-term impact of training, particularly for underperforming employees, and examining the role of emerging technologies in enhancing training effectiveness.